2005
DOI: 10.1097/01.mnh.0000165896.98372.f4
|View full text |Cite
|
Sign up to set email alerts
|

Folic acid supplementation to prevent adverse events in individuals with chronic kidney disease and end stage renal disease

Abstract: The causes of hyperhomocysteindemia in renal failure remain obscure. The possibilities include impairment of both renal and extrarenal metabolic pathways by uraemia. Hyperhomocysteindemia is associated in some but not all studies with an increased risk for cardiovascular disease. A low homocysteine may reflect malnutrition and predict a poor outcome. Folate achieves modest reductions of homocysteine in some but not all studies. There are no data to support therapy with very high-dose folic acid. Hyperhomocyste… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
4
0

Year Published

2007
2007
2016
2016

Publication Types

Select...
6
3
1

Relationship

0
10

Authors

Journals

citations
Cited by 19 publications
(6 citation statements)
references
References 41 publications
2
4
0
Order By: Relevance
“…This is in agreement with other investigators who found no effect of folic acid on EDV, in spite of lowering homocysteine level, as hyperhomocysteinemia impairs endothelial function, which is not adequately reversed by folate [37][38][39].…”
Section: Discussionsupporting
confidence: 92%
“…This is in agreement with other investigators who found no effect of folic acid on EDV, in spite of lowering homocysteine level, as hyperhomocysteinemia impairs endothelial function, which is not adequately reversed by folate [37][38][39].…”
Section: Discussionsupporting
confidence: 92%
“…Recent trials in the general population indicate that lowering homocysteine with the vitamins indicated above does not lower rates of CVD events 26 . Emerging data in patients with CKD also confirm this concept 27 . So despite the epidemiologic and pathophysiologic data on homocysteine and CVD, it appears that this protein will not be a clinical target in the future.…”
Section: Dyslipidemiassupporting
confidence: 59%
“…Both F and ADMA play an important role in determining endothelium-dependent vasodilatation end-HD, suggesting that a reduced loss of F through the dialysis membrane and ⁄ or an increased elimination of ADMA might provide potential beneficial effects on endothelial function. F supplementation has been proposed as a safe and effective interventional strategy to slow the progression of vascular disease and to reduce cardiovascular morbidity and mortality in ESRD [40]. The initial argument supporting the use of F is based on the tHcy-lowering effects of this B-vitamin [41].…”
Section: Discussionmentioning
confidence: 99%